Measurement of the photo-pump strength of the 3d-5f transitions in the automatically line matched Ni-like Sm photo-pumped X-ray laser - Norreys, P; Zhang, J; Cairns, G; Djaoui, A; Dwivedi, L; Key, M; Kodama, R; Krishnan, J; Lewis, C; Neely, D; O'Neill, D; Pert, G; et al. (1993)
The photo-pump strengths of both the ((3d 4) 0(3d 6) 0) 0 - (((3d 3) 3/2(3d 6) 0) 3/2(5f) 5/2) 1 and the ((3d 4) 0(3d 6) 0) 0 - (((3d 4) 0(3d 5) 5/2) 5/2(5f) 7/2) 1 transitions in Ni-like Sm 34+ have been measured as 2.4*10(-4) and 2.4*10(-4) photons/mode respectively. The implications of the measurement are briefly discussed in a comparison of the merits of automatically line matched photo-pump scheme to those of the collisional excitation Ni-like Sm(+34) scheme. © 1993 IOP Publishing Ltd.